2018
DOI: 10.1159/000494247
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Postural Stability and Hearing Preservation after Cochlear Implantation

Abstract: Objectives: (1) To assess dynamic postural stability before and after cochlear implantation using a functional gait assessment (FGA). (2) To evaluate the correlation between loss of residual hearing and changes in dynamic postural stability after cochlear implantation. Methods: Candidates for first-sided cochlear implantation were prospectively included. The FGAs and pure-tone audiograms were performed before and 4–6 weeks after cochlear implantation. Results: Twenty-three subjects were included. Forty-eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The age at time of cochlear implantation ranged from 14 to 86 years. For four studies, the relevant data were not available directly from the published article and was sent to us by the authors (10–13). Study characteristics are summarized in Supplemental Digital Content 2 (see Table, Supplemental Digital Content 2, http://links.lww.com/MAO/B459).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The age at time of cochlear implantation ranged from 14 to 86 years. For four studies, the relevant data were not available directly from the published article and was sent to us by the authors (10–13). Study characteristics are summarized in Supplemental Digital Content 2 (see Table, Supplemental Digital Content 2, http://links.lww.com/MAO/B459).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 44 of 67 studies reported both preimplantation and postimplantation audiological outcomes involving at least 309 patients, and improvements were reported in all but 5 of these studies. Of the five studies, one study reported one patient who became a nonuser of his cochlear implant from 1 month postoperatively (21), the second study had only 4-week postimplant follow-up and reported no response on PTA at all frequencies (11), and the third study reported one patient who had no significant improvement on speech perception tests, but the patient was reported to feel that the implant enhanced his awareness of sound and lipreading skills and wore the implant daily (41). The two remaining studies are likely to contain overlapping patients, and both report findings as the number of patients who were below the 25th percentile or below the mean cohort score, and as such, it is not possible to assess preimplant versus postimplant outcomes (8,9,27).…”
Section: Audiological Outcomes and Promsmentioning
confidence: 99%
See 2 more Smart Citations